Comparative physiological and transcriptomics analysis revealed crucial mechanisms of silicon-mediated tolerance to iron deficiency in tomato - Shi, Yu; Guo, Shuxun; Zhao, Xin; Xu, Mengzhu; Xu, Jin; Xing, Guoming; Zhang, Yi; Ahammed, Golam Jalal (Frontiers in Plant Science, 2022)
Iron (Fe) deficiency is a common abiotic stress in plants grown in alkaline soil that causes leaf chlorosis and affects root development due to low plant-available Fe concentration. Silicon (Si) is a beneficial element for plant growth and can also improve plant tolerance to abiotic stress. However, the effect of Si and regulatory mechanisms on tomato plant growth under Fe deficiency remain largely unclear. Here, we examined the effect of Si application on the photosynthetic capacity, antioxidant defense, sugar metabolism, and organic acid contents under Fe deficiency in tomato plants. The results showed that Si application promoted plant growth by increasing photosynthetic capacity, strengthening antioxidant defense, and reprogramming sugar metabolism. Transcriptomics analysis (RNA-seq) showed that Si application under Fe deficiency up-regulated the expression of genes related to antioxidant defense, carbohydrate metabolism and organic acid synthesis. In addition, Si application under Fe deficiency increased Fe distribution to leaves and roots. Combined with physiological assessment and molecular analysis, these findings suggest that Si application can effectively increase plant tolerance to low Fe stress and thus can be implicated in agronomic management of Fe deficiency for sustainable crop production. Moreover, these findings provide important information for further exploring the genes and underlying regulatory mechanisms of Si-mediated low Fe stress tolerance in crop plants.